THE EFFECTS OF READING INTEREST AND VOCABULARY MASTERY TOWARDS DESCRIPTION WRITING SKILL - Neneng Hasanah (Universitas Indraprasta PGRI, 2019)
Vocabulary Mastery towards Description Writing Skills. The research method used is survey method. The sample was taken as many as 85 students with simple random technique. Data collection was done by direct questionnaire to sample. Data analysis using descriptive statistics such as finding mean, median, standard deviation, and inferential statistic is to find simple and double correlation coefficient followed by correlation coefficient significance test with t test. This study was conducted on March 1 to July 30, 2018. The results showed: (1) There is a significant and simultaneous effect of Reading Interest and Vocabulary Mastery together towards Desctiption Writing Skills of SMP Negeri students in Bekasi City. This is evidenced by the sig score of 0.000 <0.05, and the score of F test= 9,774. While the magnitude of simultaneous effect of Reading Interest and Vocabulary Mastery together towards Description Writing Skills are shown by the coefficient of determination as much as 19.3% and the rest of 80.7% effected by other variables. (2) There is a significant effect of Reading Interest towards description writing skill of SMP Negeri students in Bekasi City. This is evidenced by the sig score of 0.001 <0.05, and the score of t test : 3.592. (3) There is a significant effect of Vocabulary Mastery towards Description Writing Skills of SMP Negeri students in Bekasi city. This is evidenced by the sig score of 0.040 <0.05, the score of t test: 2.085. Keywords: Reading Interest, Vocabulary Mastery, Description Writing Skill